Comment of the authors on the article «The contribution of various mechanisms to mRNA diversity of human fusion oncogene RUNX1-RUNX1T1» - Ilyushonak, Ilya M.; Polkhovsky, Lev I.; Grinev, Vasily V. (Experimental Biology and Biotechnology, 2020)
The main topic of this brief communication is the critical review of flaws, found in the original article «The contribution of various mechanisms to mRNA diversity of human fusion oncogene RUNX1-RUNX1T1», which was published in «Journal of the Belarusian State University. Biology» (2019, No. 2). Also authors provide new results obtained since publication.